2006
DOI: 10.1016/j.juro.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast Enhanced, Pelvic Phased Array Magnetic Resonance Imaging of Localized Prostate Cancer for Predicting Tumor Volume: Correlation With Radical Prostatectomy Findings

Abstract: Pre-biopsy pelvic phased array dynamic contrast enhanced magnetic resonance imaging is an accurate technique for detecting and quantifying intracapsular transition or peripheral zone tumor foci greater than 0.2 cc. It has promising implications for cancer detection, prognosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
199
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(209 citation statements)
references
References 21 publications
6
199
1
3
Order By: Relevance
“…Reports on DCE MRI performance in the TZ are controversial. Some published results 14,19 suggested indeed a potential value of DCE in the TZ, although other studies failed. 20,21 In our series, ADC (provided by DW imaging) was the only parameter that improved performance when combined to T2W.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on DCE MRI performance in the TZ are controversial. Some published results 14,19 suggested indeed a potential value of DCE in the TZ, although other studies failed. 20,21 In our series, ADC (provided by DW imaging) was the only parameter that improved performance when combined to T2W.…”
Section: Discussionmentioning
confidence: 99%
“…In DCE-MRI, the distribution of the contrast agent is repeatedly evaluated, allowing the evaluation of the tumor microcirculation in vivo and enabling the malignancy or benignancy of the tumor to be quantitatively distinguished (6,7). A number of previous studies have shown the diagnostic value of DCE-MRI for prostate cancer (8)(9)(10), for the evaluation of pancreatic cancer (11), and for evaluating the efficacy of cancer drugs (12)(13)(14). Only one previous study has used DCE-MRI to evaluate the tumor drug response in colorectal cancer (15), and, at present, no published studies have been concerned with the diagnostic value of DCE-MRI for rectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…While defining the anatomic extent of prostate cancer at presentation remains under investigation (5) and important in guiding management, the ability to define tumor response to neoadjuvant therapy based on imaging remains a high priority because it provides the early identification of men with disease that is resistant to current standards of care. After these men are identified, they would be eligible for entry to randomized clinical trials designed to evaluate the impact on survival of adding therapies aimed at overcoming treatment resistance to the current standards of practice.…”
Section: Introductionmentioning
confidence: 99%